Handbook of steroids (New York Hayle Medical, 2023)
Steroids are organic compounds having four rings arranged to their structure in a specific molecular configuration. There are two main functions of a steroid, i.e., to function as an important component of cell membranes which alter membrane fluidity, and to function as a signaling molecule. Most steroids are found in animals, plants, and fungi. The process through which the steroids are generated from cholesterol and changed into other steroids is known as steroidogenesis. The topics included in this book on steroids are of utmost significance and bound to provide incredible insights to readers. It unfolds the innovative aspects of steroids which will be crucial for the detailed study of the subject. For all readers who are interested in the study of steroids, the case studies included in this book will serve as an excellent guide to develop a comprehensive understanding.
Keywords: Steroids; Steroids-Drugs; Mason, Dwyane ed